Fiscal federalism, taxation and grants - Martín Gonzalez-Eiras; Dirk Niepelt (Swiss National Bank, Study Center Gerzensee, 2016)
We propose a theory of tax centralization and inter governmental grants in politico-economic equilibrium. The cost of taxation differs across levels of government because voters internalize general equilibrium effects at the central but not at the local level. This renders the degree of tax centralization and the tax burden determinate even if none of the traditional, expenditure-related motives for centralization considered in the fiscal federalism literature is present. If central and local spending are complements and the trade-off between the cost of taxation and the benefit of spending is perceived differently across levels of government, inter governmental grants become relevant. Calibrated to U.S. data, our model helps to explain the introduction of federal grants at the time of the New Deal, and their increase up to the turn of the twenty-first century. Grants are predicted to increase to approximately 5.5% of GDP by 2060.
Keywords: D72; E62; H41; H77; 330; Fiscal policy; Federalism; Politico-economic equilibrium; Markov equilibrium; Public goods; Grants; Political Economy